Letter to the Editor: Additional considerations for addressing pain in people living with cystic fibrosis - Ward, Anastasia; Mauleon, Ramil; Ooi, Chee Y.; Rosić, Nedeljka (Elsevier, 2025)
We have read with interest and express our agreement with the recently published “Addressing pain in people living with cystic fibrosis: Cystic fibrosis foundation evidence-informed guidelines” [2]. Dellon and colleagues have published a timely Cystic Fibrosis Foundation paper outlining recommendations and evidence-informed guidelines on addressing pain in people with cystic fibrosis (pwCF) [2]. These guidelines, derived from co-design methodologies, provide in-depth recommendations on managing pain in CF and intend to guide various stakeholders or healthcare practitioners at all stages of their patients’ development.